Clothed wax effigies: construction materials, challenges and suggestions for preventive conservation - Karydis, Christos (2021)
Wax effigies, fully dressed life-size models of human figures, have been constructed since the medieval times. The construction materials of historical effigies differ to the contemporary ones, yet the construction process of the wax parts has more or less remained unchanged over the centuries. This paper starts with the history, construction materials and manufacture techniques of wax effigies. The inseparable relation of the wax effigies and their costumes is explained, and the characteristics and deterioration agents of their most important construction materials are presented in order to understand their needs for preservation, with emphasis on wax and fabrics. The aim of this paper is to suggest preventive conservation guidelines for wax effigies, with proposals for appropriate environmental conditions during display and storage, and suggestions for proper handling, storage and transportation. Advice for disaster preparedness and actions in cases of emergency situations is also provided.   Received: 2020-1-28 Revised: 2020-6-16 Accepted: 2020-6-30 Online: 2020-8-19 Publication: 2021-2-10